Economic analysis / Sheikh Muhammad Shazwan S. Shahrin ... [et al.] - S. Shahrin, Sheikh Muhammad Shazwan; Saifuzzaman, Thaqif Umair; Razali, Muhammad Adib Mahfuz; Rashdan, Muhammad Afiq; Tuan Anuar, Tuan Mohammad Azamuddin; Mohd Rosmari, Muhammad Afiq Aiman (2019)
The first thing in this final year report is the economic analysis. This is to identify which country that a business to invest in. There are three types of the countries in this study which are, developed countries, regional countries (ASEAN) and third world countries. The countries are Germany, Japan, USA, Netherlands, Thailand, Vietnam, Indonesia, Singapore, Togo, Madagascar and Mozambique. The aspects in this study are, GDP rate, inflation rate, interest rate and unemployment rate. There is also the analysis of the Malaysian economy, which adds more the balance of payment, rate of employment, import, export, level of production, monetary policy and future expectation.